TAS2R20 variants confer dietary adaptation to high‐quercitrin bamboo leaves in Qinling giant pandas. Issue 12 (4th May 2020) - Hu, Xiangxu; Wang, Guan; Shan, Lei; Sun, Shuyan; Hu, Yibo; Wei, Fuwen
Abstract: Sensitivity to bitter tastes provides animals with an important means of interacting with their environment and thus, influences their dietary preferences. Genetic variants encoding functionally distinct receptor types contribute to variation in bitter taste sensitivity. Our previous study showed that two nonsynonymous sites, A52V and Q296H, in the TAS2R20 gene are directionally selected in giant pandas from the Qinling Mountains, which are speculated to be the causative base‐pair changes of Qinling pandas for the higher preference for bamboo leaves in comparison with other pandas. Here, we used functional expression in engineered cells to identify agonists of pTAS2R20 (i.e., giant panda's TAS2R20) and interrogated the differences in perception in the in vitro responses of pTAS2R20 variants to the agonists. Our results show that pTAS2R20 is specifically activated by quercitrin and that pTAS2R20 variants exhibit differences in the sensitivity of their response to the agonist. Compared with pTAS2R20 in pandas from other areas, the receptor variant with A52V and Q296H, which is most commonly found in Qinling pandas, confers a significantly decreased sensitivity to quercitrin. We subsequently quantified the quercitrin content of the leaves of bamboo distributed in the Qinling Mountains, which was found to be significantly higher than that of the leaves of bamboo from panda habitats in other areas. Our results suggest that the decreased sensitivity to quercitrin in Qinling pandas results in higher‐quercitrin‐containing bamboo leaves to be tasting less bitter to them and thus, influences their dietary preference. This study illustrates the genetic adaptation of Qinling pandas to their environments and provides a fine example of the functional effects of directional selection in the giant panda. Abstract : Sensitivity to bitter tastes provides animals with an important means of interacting with their environment and thus, influences their dietary preferences. TAS2R20 variants confer dietary adaptation to high‐quercitrin bamboo leaves in Qinling giant pandas. The decreased sensitivity to quercitrin in Qinling pandas results in higher‐quercitrin‐containing bamboo leaves to be tasting less bitter to them and thus, influences their dietary preference.